Genetic evaluation including maternal effects in Large White Yorkshire × desi crossbred pigs under hot and humid conditions of India - P JAYASREE; S N SIVASELVAM; R VENKATARAMANAN; S MEENAKSHI SUNDARAM; K V GOWRIMANOKARI; V ARTHY; D BALASUBRAMANYAM (Indian Journal of Animal Sciences, 2019)
A study was conducted to evaluate the individual and sow performance traits of Large White Yorkshire × desi crossbred pigs at All India Co-ordinated Research Project on Pigs (AICRP), Kattupakkam. The genetic groups studied were 50% LWY (100% LWY × 100% desi), 50% LWY inter se (50% LWY 50% desi × 50% LWY 50% desi), 75% LWY (100% LWY × 50% LWY 50% desi) and 75% LWY inter se (75% LWY 25% desi × 75% LWY 25% desi). The (co)variance components for different traits were estimated by restricted maximum likelihood method (REML). The average inbreeding in the whole population was 5.4%. Maternal genetic and common litter effects were important random sources of variation in individual traits. The least-squares mean for birth weight (BW), weaning weight (WW), average daily gain up to weaning (ADG), market weight (MW), pre-weaning mortality (PWM), age at first farrowing (AFF), litter size at birth (LSAB), litter weight at birth (LWAB), litter size at weaning (LSAW), litter weight at weaning (LWAW) and farrowing interval (FI) were 1.079 kg, 7.906 kg, 142.238 g, 8.4%, 62.208 kg, 456.829 days, 197.994 days, 6.792, 8.174 kg, 6.347 and 60.649 kg, respectively, and the direct heritability obtained through the best model were 0.069, 0.015, 0.012, 0.031, 0.291, 0.019, 0.173, 0.257, 0.076 and 0.157, respectively. The repeatability estimates for LWAB, LSAW, LWAW and FI were 0.265, 0.258, 0.263 and 0.762, respectively. The 75% LWY were better in terms of production and reproduction traits and the high heritability for litter traits provided good scope for improvement.